The Effect of Price on Customer Satisfaction Mediated by Brand Image - Fakhrizza Anfasa Ramadhan Fakhrizza; Marsudi Marsudi; Ardik Praharjo (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the effect of price on brand image and its impact on Go-Jek customer satisfaction via Go-Ride services. This type of research is explanatory research with a quantitative approach. The population in this study was UMM students with a sample of UMM students from the Faculty of Economics and Business, Management Department. 100 students were selected by the purposive sampling method while data were collected using a questionnaire and then analyzed with SmartPLS 3.0. The results of this study show that price has no significant effect on consumer satisfaction. Price affects the brand image and brand image affects consumer satisfaction. Indirectly, the price has a significant effect on consumer satisfaction through brand image.